Association of N-nitrosodimethylamine exposure with cognitive impairment based on the clues of mice and humans - Liu, Wei; Huang, Jia; Yan, Zhi; Lin, Yankui; Huang, Guanqin; Chen, Xiao; Wang, Zhou; Spencer, Peter S.; Liu, Jianjun (Frontiers in Aging Neuroscience, 2023)
N-nitrosodimethylamine (NDMA) is an environmental and food contaminant, but limited data to concern whether NDMA has adverse effects on the brain. This study first determined the concentration of NDMA in foods from aquaculture markets in Shenzhen, then analyzed the effects on C57BL/6 mice and further evaluated on the urine samples of elderly Chinese residents with normal cognition (NC, n = 144), cognitive decline (CD, n = 116) and mild cognitive impairment (MCI, n = 123). The excessive rate of NDMA in foods was 3.32% (27/813), with a exceeding range of 4.78–131.00 μg/kg. Behavioral tests showed that 60 days treatment of mice with 3 mg/kg NDMA reduced cognitive performance. Cognitive impairment in human was significantly associated with sex, educational levels, length of residence in Shenzhen, household registration, passive smoking, rice, fresh vegetables, bacon products. NDMA was detected in 55.4% (212/383) of urine samples, with a median concentration of 0.23 μg/L (1.20 × 10 –7–157.39 μg/L). The median concentration for NC, CD and MCI were 0.32, 0.27, and 0 μg/L, respectively. The urinary NDMA concentration had a strong negative correlation with cognitive impairment (Kendall’s Tau-b = −0.89, P = 0.024). The median estimated daily intake (EDI) of NDMA was determined to be 6.63 ng/kg-bw/day. Taken together, there appears to be an association between NDMA and human and murine cognition, which provides a new clue to Alzheimer’s disease (AD).